Fall risk-increasing drugs and associated health outcomes among community-dwelling older patients: A cross-sectional study in Croatian cohort of the EuroAgeism H2020 project - Paar Elizabeta; De Lai Eleonora; Držaić Margita; Kummer Ingrid; Bužančić Iva; Hadžiabdić Maja Ortner; Brkic Jovana; Fialová Daniela (Acta Pharmaceutica)
Our study aimed to assess the prevalence of fall risk-increasing drugs (FRIDs) in a sample of community-residing older patients in Croatia and its association with negative health outcomes. An observational, cross-sectional study was conducted on older patients (65+) visiting community pharmacies in three regionally different study sites in Croatia. Data were collected using a questionnaire developed for that purpose and included components of comprehensive geriatric assessment. Prevalence of FRIDs was identified using the “Screening Tool of Older Persons Prescriptions in older adults with high fall risk” (STOPPFall). In the sample of 407 participants (median age 73 (IQR 69–70) years; 63.9 % females), 79.1 % used at least one FRID. The most common drug classes were diuretics, benzodiazepines, and opioids (in 51.1 %, 38.1 %, and 17.2 % participants, respectively). More FRIDs were prescribed to the oldest old patients (85+) and participants from poorer regions of Croatia (Slavonia) (p < 0.05). Exposition to FRIDs was identified as the significant risk factor associated with falls (OR = 1.24 (1.04–1.50); p = 0.020) and higher health-care utilization (OR = 1.29 (1.10–1.51); p = 0.001). Our study highlights the need for rationalization of FRID use. To reduce the unnecessary exposure to FRIDs in older adults, health-care professionals must consider high individualization of medication schemes regarding selection, dosing, and combinations of only necessary FRIDs.